Literacy and social migration, in the Karl Weiss Schereiber commemorative sculpture by Miguel Baca Rossi - Cruz Salazar, Alexander (2025)
This article examines the memorial sculpture to Karl Philipp Weiss Schereiber, a key figure in Chiclayo’s identity, linked to socioeconomic, migratory and territorial development movements that included the implementation of schools to reduce illiteracy and public spaces to house sculptures. This study aims to answer how literacy and social migration were factors in the development of public art in Chiclayo at the beginning of the 20th century. It also reflects on social conflicts and German immigration in northern Peru, analyzes urban growth and new scenarios for the development of public art and, finally, explains the importance of Karl Weiss in the educational development of the region; whose influence will be decisive in Miguel Baca Rossi. Pedestrian sculpture is a testimony of the relationship between school-teacher-student.